2000
DOI: 10.1002/etc.5620190217
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity and toxicokinetics of ddt and its major metabolites in freshwater amphipods

Abstract: The toxicity and toxicokinetics of radiolabeled DDT and its major degradation products, dichlorodiphenyldichloroethane (DDD) and dichlorodiphenyldichloroethylene (DDE), were determined for the amphipods Hyalella azteca and Diporeia spp. in water‐only static renewal exposures. Comparison of the water and tissue concentrations associated with decreased survival revealed large differences in toxicity among the three compounds. In H. azteca, the ratio of the 10‐d LR50 values (median lethal tissue residue) for DDT:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 46 publications
(59 reference statements)
9
59
1
1
Order By: Relevance
“…To model the toxicity postexposure using discrete interval analysis, we first estimated DDE body residue using toxicokinetics based on previously published concentration depen- dence [13]. Uptake coefficients were predicted from concentration using the regression ln k u 5 20.062 6 0.008 ?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To model the toxicity postexposure using discrete interval analysis, we first estimated DDE body residue using toxicokinetics based on previously published concentration depen- dence [13]. Uptake coefficients were predicted from concentration using the regression ln k u 5 20.062 6 0.008 ?…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have not found that H. azteca can biotransform DDE [13]. Animals were blotted dry, weighed, transferred to a 3-ml scintillation cocktail (3a70b, Research Products International), and sonicated for 1 min with a Tekmar high-intensity probe (375 W at 20% power).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relationship between percent survival of the freshwater amphipod Hyalella azteca and their dichlorodiphenyldichloroethylene (DDE) body residues (fromLotufo et al, 2000).…”
mentioning
confidence: 99%